2003
DOI: 10.1021/op0256183
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Asymmetric Hydrogenation of 2-Methylenesuccinamic Acid Using a Rh-DuPHOS Catalyst

Abstract: An extremely efficient route to highly enantiomerically enriched 2-methylsuccinamic acid via asymmetric hydrogenation has been developed. By using [(S,S)-Et-DuPHOS Rh COD]BF 4 as the precatalyst under a set of broadly optimised process parameters, (R)-2-methylsuccinamic acid was obtained in 96% ee at a substrate-to-catalyst ratio (S/C) of 100000 (average turnover frequency ∼13000 h -1 ). The exclusion of chloridecontaining contaminants in the substrate was found to be crucial in obtaining exceptionally low cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…Upon testing, the crude product of the reaction between BINOL-based chlorophosphite and piperidine in the rhodium-catalysed hydrogenation of methyl 2-acetamido-cinnamate, we found that reaction was much slower and the product was obtained in only 60 % ee, whereas 99 % was obtained with pure 1 d. Evidently, the reason for this poor performance is the presence of a stoichiometric amount of chloride, which functions as a catalyst poison. [24] Remarkably, performing the coupling reaction in toluene and removing the salt by a simple filtration led to a crude ligand, which after removal of toluene performed quite satisfactorily in the above hydrogenation reaction. In this case, the conversion went to 100 % and the product was obtained with 96 % ee, which is only slightly lower as with the purified ligand.…”
Section: Instant Ligand Librariesmentioning
confidence: 99%
“…Upon testing, the crude product of the reaction between BINOL-based chlorophosphite and piperidine in the rhodium-catalysed hydrogenation of methyl 2-acetamido-cinnamate, we found that reaction was much slower and the product was obtained in only 60 % ee, whereas 99 % was obtained with pure 1 d. Evidently, the reason for this poor performance is the presence of a stoichiometric amount of chloride, which functions as a catalyst poison. [24] Remarkably, performing the coupling reaction in toluene and removing the salt by a simple filtration led to a crude ligand, which after removal of toluene performed quite satisfactorily in the above hydrogenation reaction. In this case, the conversion went to 100 % and the product was obtained with 96 % ee, which is only slightly lower as with the purified ligand.…”
Section: Instant Ligand Librariesmentioning
confidence: 99%
“…Very few good results have been reported. Cobley and coworkers reported a hydrogenation process of 2 -methylenesuccinamic acid [189] . In addition to the high enantioselectivity achieved, the fast reaction rate and high turnover number of the process was signifi cant for industrial -scale synthesis.…”
Section: Unsaturated Acids and Their Derivativesmentioning
confidence: 99%
“…RhDuPhos was used for itaconic amides by Dow/Chirotech [59,60] and gave eevalues of 96-97%, TON 100 000, TOF 13 000 h -1 at 45 8C, 10 bar. For dimethyl itaconates, Chiral Quest reported ee-values up to 99%, TON 5000, at r.t./1.5 bar using TangPhos [47], while Rh-catASium ® M (Degussa [61]) achieved ee-values up to 99%, TON 10 000, TOFs up to 40 000 h -1 at 25 8C/4 bar, and Rh-monophosphite (Lanxess [62]) gave ee-values up to 99%, TON 10 000, TOFs up to 5 000 h -1 at 0 8C/0.5 bar (ligand structures see Fig.…”
Section: Itaconic Acid Derivativesmentioning
confidence: 99%